Astrophysical Naturalness - Soker, Noam (Frontiers in Astronomy and Space Sciences, 2022)
I suggest that stars introduce mass and density scales that lead to “naturalness” in the Universe. Namely, two ratios of order unity. 1) The combination of the stellar mass scale, M*(c, ℏ, G, mp, me, e, …), with the Planck mass, MPl, and the Chandrasekhar mass leads to a ratio of order unity that reads NPl*≡MPl/(M*mp2)1/3≃0.15−3, where mp is the proton mass. 2) A system with a dynamical time equals to the nuclear life times of stars, τnuc*, has a density of ρD*(c,ℏ,G,mp,me,e,…)≡(Gτnuc*2)−1. The ratio of the dark energy density to this density is Nλ* = ρΛ/ρD* ≈ 10−7−105. Although the range is large, it is critically much smaller than the 123 orders of magnitude usually referred to when ρΛ is compered to the Planck density. In the pure fundamental particles domain there is no naturalness; either naturalness does not exist or there is a need for a new physics or new particles. The “Astrophysical Naturalness” offers a third possibility: stars introduce the combinations of, or relations among, known fundamental quantities that lead to naturalness.